PROPHETIC COMMUNICATION IN DIGITAL DA’WAH: A CASE STUDY OF USTAZ HANDY BONNY’S INSTAGRAM CONTENT - Kania Nur Hanifah Hasna; Adi Permana Sidik; Erwan Komara; Karla Safa Attallah (PT Altin Riset Publishing, 2026)
This study aims to analyze the prophetic communication approach applied in Ustaz Handy Bonny’s da’wah content on Instagram, which has attracted significant attention among young Muslim audiences. The research addresses three main questions: why prophetic communication is essential in the context of digital da’wah, how the six qaulan principles (qaulan sadiidan, qaulan balighan, qaulan maysuuran, qaulan layyinan, qaulan kariiman, and qaulan ma’ruufan) are implemented, and what forms and content of da’wah reflect these values. Using a qualitative method with a case study approach, the research employed in-depth interviews with Ustaz Handy Bonny, his media team, followers, and experts, along with observation of his Instagram content. Data analysis followed Miles and Huberman’s interactive model (reduction, display, conclusion) and triangulation for credibility. The findings show that Ustaz Handy Bonny’s da’wah reflects prophetic communication by combining clarity, emotional appeal, and ethical language, while addressing contemporary youth issues such as relationships, mental health, and spiritual awareness. However, critiques arise regarding the use of slang language, questions of credibility as a ‘hijrah ustaz’, and challenges in maintaining prophetic standards in a commercialized digital space. This study contributes to the development of Islamic communication by showing that prophetic communication provides an ethical and transformative framework for digital da’wah, balancing between popularity and spiritual depth.